Financial Auditing During Crisis: Assessing and Reporting Fraud and Going Concern Risk in Lebanon - Khalil Feghali; Reine Najem; Beverly Dawn Metcalfe (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - What is the impact of the Lebanese crisis on the financial auditing mission, mainly during assessing and reporting fraud and going concern risk? Motivation - So far, the academic research covering the Lebanese crisis is still rare. Hence, the spillover of the financial distress is an under researched area. Our aim to investigate the impact of financial and economic disruption on financial auditing mission, together with assessing and reporting fraud and going concern risk is an important contribution to risk literature. Idea - The article examines the impact of the Lebanese crisis on financial auditing mission, mainly during assessing and reporting fraud and going concern risk. More specifically, based on fraud triangle theory and bankruptcy theory, this study investigates the response of Lebanese financial auditors to the increase of fraud and going concern risk during crisis. Data - The questionnaire survey was used to collect responses from 239 external and internal auditors. Tools - Univariate descriptive statistics have been used to describe the respondents' profile, the Principal Component Analysis (PCA) as a data reduction method and the Kendall's Tau B, Anova and Logistic Regression for hypotheses testing. Findings - The empirical study suggests the presence of a significant relationship between the propagation of fraud and the going concern risk. Facing this situation, Lebanese financial auditors modified the audit reports, by issuing a going concern opinion through the adoption of a hierarchical system based on the severity of the assessed risk. Contributions - The research illustrates how regulators, shareholders and several bodies can effectively evaluate financial auditors' roles during crisis, especially in terms of fraud and going concern risk. Additionally, the findings invite several bodies to never separate fraud from going concern principle during the evaluation of the trustworthiness of financial statements, and the overall credibility of business continuity.
Keywords: G01; H12; M42; 650; Crisis; financial auditing; fraud; going concern; audit report